The Effect of Basic Disaster Management Training on Basic Training With Employee Performance as an Intervening Variable at the Human Resource Development Agency North Sumatra Province - Yurlinda; Muhammad Isa Indrawan (International Journal of Society and Law, 2024)
The purpose of this study is to find out and analyze the influence of Basic Training on Employee Competency mediated by Performance on Employees of the North Sumatra Human Resources Development Agency. This research was carried out at the North Sumatra Human Resources Development Agency. The type of research is quantitative associative. The sample in this study is 107 employees of the North Sumatra Human Resources Development Agency. The sampling technique in this study uses a saturated sample so that the entire population will be a sample of 107 people. The results of the study show that Basic Training does not have a significant influence on Employee Competence as shown by the T-Statistic value of 0.265 < 1.96 and the P Value value of 0.791 > 0.05. In the effect of Basic Training on Performance, data on T-Statistics values were obtained from 3,035 > 1.96 and P-Value values of 0.003 < 0.05 or there was an influence of Basic Training on Performance. Performance had a significant effect on Employee Competency with a T-Statistic value of 4,407 > 1.96 with a P-Value of 0.000 < 0.05. In the indirect influence, the results show that Performance has a role as an intervening variable that will explain the relationship between Basic Education and Training and Employee Competency of the North Sumatra Human Resources Development Agency. This shows that improvements in Basic Training will be able to improve performance, which in turn can also contribute to improving the Competency of Employees of the North Sumatra Human Resources Development Agency.